Cognitive and cortical network alterations in pediatric temporal lobe space-occupying lesions: an fMRI study - Hu, Bohan; Guan, Xueyi; Zhai, Huina; Han, Xu; Hu, Cuiling; Gong, Jian (Frontiers in Human Neuroscience, 2024)
BackgroundTemporal lobe mass lesions are the most common intracranial space-occupying lesions in children, among various brain lobes. The temporal lobe is critically involved in higher cognitive functions, and surgical interventions often risk causing damage to these functions. If necessary interventions and prehabilitation can be conducted preoperatively, it might be possible to achieve a larger extent of lesion resection with minimal cognitive impairment. However, research in this area has been relatively limited in the past. Our study aims to fill this gap.MethodsWe enrolled 15 children with temporal lobe mass lesions and 15 age- and gender-matched healthy children as controls. All participants underwent cognitive assessments and functional MRI scans. The cognitive testing data and functional MRI data were then analyzed and compared between the two groups.ResultsOur findings suggest that children with temporal lobe mass lesions primarily exhibit impairments in working memory and sustained attention. Multiple brain network indices were altered in the affected children, with the most prominent change being hyperactivation of the default mode network (DMN). This hyperactivation was correlated with cognitive impairments, indicating that the overactivation of the DMN might represent an inefficient compensatory mechanism within the brain’s networks.ConclusionCompared to healthy children, those with temporal lobe mass lesions experience deficits in working memory and sustained attention, and the hyperactivation of the DMN may be the underlying network mechanism driving these cognitive impairments. Our research offers a unique and clinically valuable reference for future studies on preoperative interventions and prehabilitation in this population.